2016
DOI: 10.1310/hpj5110-847
|View full text |Cite
|
Sign up to set email alerts
|

Defibrotide

Abstract: Each month, subscribers to The Formulary Monograph Service receive 5 to 6 well-documented monographs on drugs that are newly released or are in late phase 3 trials. The monographs are targeted to Pharmacy & Therapeutics Committees. Subscribers also receive monthly 1-page summary monographs on agents that are useful for agendas and pharmacy/nursing in-services. A comprehensive target drug utilization evaluation/medication use evaluation (DUE/MUE) is also provided each month. With a subscription, the monogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Various pharmacological agents are currently under investigation as potential treatments for SOS/VOD. Defibrotide, approved in many European and US, has been shown to suppress SOS/VOD by inducing TM and prostaglandin I2 in endothelial cells and by inhibiting the expression of PAI-1 (16)(17)(18). The present study focused on TM, which has recently been reported to have not only an anticoagulant effect but also a wide range of other effects, such as anti-inflammatory and angiogenic effects, and a protective effect on the vascular endothelium (29).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Various pharmacological agents are currently under investigation as potential treatments for SOS/VOD. Defibrotide, approved in many European and US, has been shown to suppress SOS/VOD by inducing TM and prostaglandin I2 in endothelial cells and by inhibiting the expression of PAI-1 (16)(17)(18). The present study focused on TM, which has recently been reported to have not only an anticoagulant effect but also a wide range of other effects, such as anti-inflammatory and angiogenic effects, and a protective effect on the vascular endothelium (29).…”
Section: Discussionmentioning
confidence: 98%
“…Although no method has yet been established for the prevention and treatment of SOS/VOD, defibrotide has been a focus of attention in other countries (16)(17)(18); however, in Japan, it cannot be used because the costs are not covered by insurance. Recently, recombinant human soluble thrombomodulin (rTM), which has been used as a therapeutic agent for the treatment of disseminated intravascular coagulation, has gained attention because of its anti-inflammatory properties and protective effect on the vascular endothelium (19).…”
mentioning
confidence: 99%
“…The agent aids to reduce cardiovascular disease risk by reducing low-density lipoprotein (LDL) cholesterol levels. Defibrotide is a polydisperse oligo-nucleotide purified from porcine intestinal mucosa that has been approved as a drug against severe hepatic veno-occlusive disease, where it acts in a complex sequenceindependent mechanism on fibrosis, angiogenesis, apoptosis, and aggregation of thrombocytes (15,16). Other nucleotide-based therapeutic approaches are currently being tested in clinical trials (17,18).…”
Section: Rnasmentioning
confidence: 99%
“…Pre-existing thrombocytopenia, and Renal failure, Patients with impaired blood clotting. Should not be given along with anticoagulants, and platelet inhibitors Hemorrhage, hypotension, interstitial lung disease, cystitis hemorrhagic, renal failure, haematuria, gastrointestinal hemorrhage Should be avoided with systemic anticoagulant or fibrinolytic therapy [78].…”
Section: Pregnancymentioning
confidence: 99%